Female Mice Have Higher Angiogenesis in Perigonadal Adipose Tissue Than Males in Response to High-Fat Diet - Rudnicki, Martina; Abdifarkosh, Ghoncheh; Rezvan, Omid; Nwadozi, Emmanuel; Roudier, Emilie; Haas, Tara L. (Frontiers in Physiology, 2018)
Background: Impaired capillary growth (angiogenesis) in skeletal muscle and adipose tissue contributes to the development of metabolic disorders in obese males. This association remains unexplored in females, despite mounting evidence that endothelial cells have sex-specific transcriptional profiles. Therefore, herein we assessed whether males and females show distinct angiogenic capacities in response to diet-induced obesity. Methods: Age-matched male and female mice were fed normal chow or high-fat obesogenic diets for 16 weeks. At the end of diet period, systemic glucose disposal was assessed as well as insulin sensitivity of skeletal muscle and visceral adipose tissue. Capillary content and the expression of angiogenic regulators were also evaluated in these tissues. Results: When placed on a high-fat diet, female mice gained less weight than males and showed a metabolic phenotype similar to NC-fed mice, contrasting with the impaired whole-body glucose metabolism observed in high-fat-fed males. However, high-fat-feeding elevated serum lipid levels similarly in male and female mice. Although skeletal muscle of high-fat–fed female mice had higher insulin sensitivity than male counterparts, no sex difference was detected in muscle capillarization. Metabolic functions of perigonadal white adipose tissue (pgWAT) were retained in high-fat-fed females, as evidenced by smaller adipocytes with preserved insulin sensitivity, greater responsiveness to isoproterenol, higher expression of adiponectin and a lower ratio of leptin:adiponectin mRNA. An enhanced browning phenotype was detected in HF-fed female adipocytes with upregulation of Ucp1 expression. PgWAT from high-fat-fed females also showed augmented capillary number and expression of endothelial cell markers, which was associated with elevated mRNA levels of pro-angiogenic mediators, including vascular endothelial growth factor A (Vegfa) and its receptor (Vegfr2), the Notch ligand Jagged-1 (Jag1) and Angiopoietin-2 (Angpt2). Conclusions: Taken together, our findings provide novel evidence that visceral adipose tissue of female mice display greater levels of pro-angiogenic factors and vascularity than males in response to high-fat diet. This phenotype is associated with preserved metabolic homeostasis at both tissue and systemic levels. Our study discloses that a thus-far-unappreciated sex-specific difference in the regulation of adipose angiogenesis may contribute to an individual’s susceptibility to developing adipose dysfunction and obesity-related metabolic disturbances.